ANALISIS KOMPETENSI PEGAWAI DINAS PENDIDIKAN KABUPATEN SUMEDANG - Indra Wahyudinata; Epi Susilawati; Muhammad Haekal; Rifqi Naufal Muzzaki; Wike Siti Dayanti (JRPA - Journal of Regional Public Administration, 2022)
This study aims to determine, obtain objective data and information regarding Competency Analysis in Improving Employee Performance at the Education Office of Sumedang Regency. In this study, using qualitative research methods with data collection, observation steps, in-depth interviews and documentation. From this research, it was found that the factors that support Competence in Improving Employee Performance at the Education Office of Sumedang Regency as a whole can be said to be quite good, but there are problems regarding the lack of ability of employees in carrying out tasks, in using technology, lack of ability or skills so that it occurs. non-conformance in dealing with competency issues. Obstacles were found regarding Competence in Improving Employee Performance at the Education Office of Sumedang Regency, namely: in terms of budget, interest or awareness of employees, facilities, and when employees face new things, lack of funds and environmental atmosphere or organizational climate that is less supportive, lack of areas of expertise expertise in the analysis phase of a problem at hand, poor capacity in thinking about complex problems, does not meet predetermined standards, errors occur if collecting data too quickly. Efforts to overcome obstacles include developing potential, learning and developing continuously, using analytical techniques in problem solving, anticipating complex problems, working beyond/meeting standards, and job opportunities are carried out accurately according to the competence of employees at the District Education Office Sumedang.